MATERIAIS DE COMPOSIÇÃO TI/PBXTI1-XO2 PARA DEGRADAÇÃO ELETROQUÍMICA FOTO-ASSISTIDA DE POLUENTES ORGÂNICOS - Fornazari,Ana Luiza de T. (2016)
Electrochemical methods are an interesting and clean alternative for the abatement of toxic organic pollutants. This paper details the study of the synthesis of electrode materials of nominal composition Ti/PbXTi1-XO2 (X = 0; 0.05; 0.10; 0.20 e 0.30) and their use as electrodes for degradation of organic pollutants using both electrochemical and photo-assisted electrochemical techniques. The results demonstrate that the materials produced are interesting from the point of view of organic removal. The application of simultaneous UV radiation with electrical current was capable of removing greater amounts of the organic load (>32% in <1 h) than the electrochemical technique alone.